Algorithm 803 a simpler macro processor. - Ward, Jr., William A. (ACM transactions on mathematical software.)
Macro processors have been in the computing tool chest since the late 1950's. Their use, though perhaps not what it was in the heyday of assembly language programming, is still widespread. In the past, producing a full-featured macro processor has required significant effort, similar to that required to implement the front-end to a compiler augmented by appropriate text substitution capabilities. The tool described here adopts a different approach. The text containing macro definitions and substitutions is, in a sense, ?compiled? to produce a program, and this program must then be executed to produce the final output.